Agency in a Deterministic World - Andrada, Gloria (Teorema. Revista Internacional de Filosofía, 2025)
In Determined: A Science of Life Without Free Will, Sapolsky argues that determinism and free will are incompatible, emphasizing that our actions are shaped by genetics, brain chemistry, and environment, not conscious choice. This view challenges traditional ideas of moral responsibility, suggesting that people should not be blamed for actions they couldn’t control due to biological and social influences. Despite this, I argue that Sapolsky overlooks a potential space for agency within a deterministic framework. He examines conditioned learning and I believe this opens the door for both individual and collective agency. If behavior can be influenced by external forces, there may be room for us to shape our actions and society through environmental interventions.